Scripta Manent: Notes on a Book. - CHOURMOUZIADI, ANASTASIA (Public Archaeology, 2009)
Monitoring public perceptions of an ongoing archaeological project, although often discussed, is still a marginal activity, overshadowed by excavation and laboratory routines. The problem remains even if the research team is strongly orientated towards the broadest possible dissemination of the archaeological information, as in the case of Dispilio, a Neolithic lakeside settlement in northern Greece. A visitors' book, kept since 1996, illustrates in a colourful way the visitors' impressions, offering at the same time a glimpse of the complex mechanisms that forge these impressions. Moreover, a close examination of the written comments makes it clear that there is much more to be 'read' underneath their obvious flattering remarks, and that they should be incorporated in a more systematic ethnographic study of the archaeological visit's performance.